1984
DOI: 10.1007/bf00226952
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue influences on patterns of epithelial architecture and keratinization in skin and oral mucosa of the adult mouse

Abstract: Epithelial-mesenchymal interactions play an important role during embryogenesis but it is uncertain whether such interactions influence the maintenance of epithelial structure in the adult. To examine this problem, separated epithelial and connective tissue components of skin and mucosae from various regions of adult mice were homo-or heterotypically recombined and transplanted to histo-compatible hosts. The patterns of tissue architecture and keratinization of the resultant epithelia were examined for changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 25 publications
3
65
0
1
Order By: Relevance
“…The epithelial cell monolayer produced greater amounts of differentiating K10 than did the kEHOM and nkEHOM following contact with C. albicans. This is in agreement with previously reported results indicating that K10 expression varies with cell type [39], developmental stage [40], tissue differentiation [41], and pathological changes [42]. Given the effect of C. albicans on K10 production, we investigated the effect on proliferative and basal layer K14 and showed that the yeast did not affect K14 production.…”
Section: Discussionsupporting
confidence: 91%
“…The epithelial cell monolayer produced greater amounts of differentiating K10 than did the kEHOM and nkEHOM following contact with C. albicans. This is in agreement with previously reported results indicating that K10 expression varies with cell type [39], developmental stage [40], tissue differentiation [41], and pathological changes [42]. Given the effect of C. albicans on K10 production, we investigated the effect on proliferative and basal layer K14 and showed that the yeast did not affect K14 production.…”
Section: Discussionsupporting
confidence: 91%
“…Even though clinical evidence is lacking, it may very well be possible to obtain oral site-differentiated epithelium by culturing keratinocytes from different places in the oral cavity. On the other hand, it has previously been shown, in several studies, that the dermis does indeed play a role in epidermal morphology and cytodifferentiation (Karring et al, 1975;Mackenzie and Hill, 1984;Hill and Mackenzie, 1984). Instead of culturing, the authors transplanted the epithelium and underlying connective tissue in various combinations among histocompatible hosts to various sites.…”
Section: Advantages Of Keratinocyte Sheet Grafting From a Clinical Pementioning
confidence: 99%
“…Cultured keratinocytes show full differentiation only if associated with a connective tissue or with fibroblasts (Rheinwald and Green, 1975;Mackenzie and Hill, 1984;Mackenzie and Dabelsteen, 1987). Native collagen alone may promote keratinocyte attachment and proliferation, but not differentiation (Holbrook and Hennings, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Melby and Karasek (1973) proposed two mechanisms to explain the influence of connective tissue on epithelial cells: 1) the connective tissue provides a physical substrate for attachment and orientation of epidermal basal cells; and 2) the connective tissue cells synthesize diffusible proteins that influence both growth and differentiation of epithelial cells. That diffusible factors of dermal origin facilitate growth and differentiation of the epithelial cells has long been considered relevant (Karring et al, 1975;Mackenzie and Fusenig, 1983;Mackenzie and Hill, 1984;Coulomb, 1989;Mackenzie et al, 1993). Mackenzie and Fusenig (1983) showed that even if keratinocytes have no direct contact with connective tissue, they still show full differentiation, thereby demonstrating that diffusible dermal products contribute to the differentiation of cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation